LEVERAGING THE POTENTIAL OF DIGITAL ADMINISTRATIVE SERVICES AS A STRATEGIC FACTOR FOR SUPPORTING ENTREPRENEURSHIP WITHIN THE FRAMEWORK OF UKRAINE’S EUROPEAN INTEGRATION COURSE (Coordinates of Public Administration, 2026)
In the current context of public administration reform and the implementation of Ukraine's European integration course, Digital Administrative Services (DAS) acquire strategic significance as a key driver for the accelerated development of business entities. The article analyzes the integral potential of DAS and identifies key directions for its maximization to ensure strategic business support.The study investigates the institutional and programmatic mechanisms of DAS influence on the formation of a favorable environment, particularly through tools for minimizing transaction costs, enhancing institutional transparency, and unifying regulatory procedures. Special attention is paid to the transformation of the state's role from administrative controller to cognitive partner through the introduction of a predictive service model and proactive service delivery (the «Data Once» principle). An analysis of systemic barriers is performed, and the necessity of an inclusive strategy for DAS implementation is substantiated. The article formulates recommendations for public administration bodies regarding the use of DAS as a strategic infrastructure that supports the digital competitiveness of the national economy in the context of global transformations. Digital Administrative Services (DAS) function as an institutional innovation that ensures a radical reduction in transaction costs and increased regulatory predictability for business entities, requiring the state to transition to a proactive management model and a strategy for overcoming digital exclusion to maintain economic competitiveness.